Generation of a high quality library of bioactive filamentous actinomycetes from extreme biomes using a culture-based bioprospecting strategy - Świecimska, Magdalena; Golińska, Patrycja; Goodfellow, Michael (Frontiers in Microbiology, 2023)
A culture-based bioprospecting strategy was used to isolate and screen filamentous actinomycetes from three poorly studied extreme biomes. Actinomycetes representing different colony types growing on selective media inoculated with environmental suspensions prepared from high-altitude, hyper-arid Atacama Desert soils, a saline soil from India and from a Polish pine forest soil were assigned to taxonomically predictive groups based on characteristic pigments formed on oatmeal agar. Comparative 16S rRNA gene sequencing analyses on 115 representatives of the resultant colour-groups and their immediate phylogenetic neighbours showed that most belonged to either rare or novel species that represented twelve genera. Representative isolates from the three extreme biomes showed different patterns of taxonomic diversity and bioactivity profiles. Many of the isolates produced bioactive compounds that inhibited the growth of one or more strains from a panel of nine wild strains in standard antimicrobial assays and produced bioactive compounds that promote plant growth. Actinomycetes from the litter and mineral horizons of the pine forest, including acidotolerant and acidophilic strains belonging to the genera Actinacidiphila, Streptacidiphilus and Streptomyces, showed a remarkable ability to inhibit the growth of diverse fungal and oomycete plant pathogens. It can be concluded that selective isolation and characterization of dereplicated filamentous actinomycetes from several extreme biomes is a practical way of generating high quality actinomycete strain libraries for agricultural, industrial and medical biotechnology.